Versão brasileira do Dizziness Handicap Inventory - Castro, Ana Sílvia Oliveira De (2007)
BACKGROUND: impact of dizziness on life quality (LQ). AIM: to adapt the Dizziness Handicap Inventory (DHI) for application in the Brazilian population; to assess its reproducibility; and to describe the results obtained in patients with chronic dizziness. METHOD: The DHI was initially applied in 45 patients with chronic dizziness and with a clinical diagnosis of vestibular syndrome. The application followed the stages of translation - from English to Portuguese - and linguistic adaptation, grammatical and idiomatic equivalence review and evaluation of its intra and inter-researchers reproducibility. Reproducibility was assessed by using the Wilcoxon Test for two dependent samples, P < 0.05. The questionnaire was applied on 250 patients with chronic vestibular syndrome in order to evaluate the impact of dizziness on LQ. RESULTS: The Brazilian version of the DHI (Brazilian DHI) was well comprehended by the studied population and no statistically significant difference was found in the inter-researcher (P = 0.418) and intra-researcher (P = 0.244) reproducibility. All of the studied patients presented a loss in LQ due to dizziness. Aspects which were most affected were the physical ones, followed by, in a decreasing order, the functional and the emotional ones. Functional aspects were more compromised in older individuals. No association was verified between gender and the overall mean scores of the DHI and between gender and the mean scores of each aspect assessed by the DHI. CONCLUSION: the DHI was culturally adapted for application in the Brazilian population (Brazilian DHI). This instrument was considered to be a reliable tool to evaluate the impact of dizziness on LQ. Patients with chronic dizziness and with clinical diagnosis of vestibular syndrome presented a loss in LQ, due to this symptom. This loss was verified by the application of the Brazilian DHI. Physical aspects were the most compromised.